Market design of regional flexibility markets: A classification metric for flexibility products and its application to German prototypical flexibility markets - Erik Heilmann; Nikolai Klempp; Heike Wetzel (Philipps-University Marburg, School of Business and Economics, 2020)
With a growing number of distributed energy resources, the electricity network is challenged with a higher quantity of technical problems such as capacity congestions and over- or under-voltages. One often-discussed approach to solve these problems, especially in the European zonal electricity system, is regional exibility markets. We provide a novel metric for the design of exibility products by combining technical requirements with a background in auction theory. This is a valuable contribution to the discussion of regional exibility markets, which currently occurs on a largely technical or conceptual level. The metric structures 23 product parameters in four stages of different abstraction levels. By applying this metric to five exibility market approaches used in current German research projects, we demonstrate its usability for consistent description and comparison of exibility products. Therefore, the metric we have developed, is a powerful instrument for structured analysis and assessment of the vast diversity of approaches to exibility markets and products at a high level of detail. This metric can empower national and international policy makers and practitioners in developing and assessing exibility markets holistically and can help to simplify the implementation of best-practice solutions.
Keywords: D47; L94; Q41; 330; smart markets; market design; electricity product design; flexibility market